1962
DOI: 10.1071/bi9620720
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between the Responses of Wool Growth and Body Weight to Changes in Feed Intake

Abstract: SummaryThe wool growth responses to changes in feed intake are related to the changes produced in body weight. The relation is expressed by the equation W = Ei-kG, where W = wool growth rate, i = feed intake rate, G = rate of body weight change, and E and k are constants. The ratio of E to k in sheep of different productive efficiency was found to be constant.Evidence is presented that this equation indicates a relation between wool growth and metabolic rate, both possibly being responses to changes in endocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
19
1

Year Published

1967
1967
1988
1988

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 7 publications
5
19
1
Order By: Relevance
“…In these experiments the constituents of the feed are sometimes held unchanged, in which case the intake can be regarded simply as gross energy intake (Ferguson 1962), while others seek to explore the effects of various constituents-for example, the protein fraction of the diet (Black et al 1973). The analysis of data carried out in order to relate wool growth to energy intake has usually only involved linear regression to test time-independent equations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In these experiments the constituents of the feed are sometimes held unchanged, in which case the intake can be regarded simply as gross energy intake (Ferguson 1962), while others seek to explore the effects of various constituents-for example, the protein fraction of the diet (Black et al 1973). The analysis of data carried out in order to relate wool growth to energy intake has usually only involved linear regression to test time-independent equations.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper a more general approach is used to analyse the results reported by Ferguson (1962). The relationship between wool growth and intake in this approach is assumed to be time-dependent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, and contrary to the realimentation. views of Ferguson (1962), Black, Robards & Thomas (1973 suggested that the rate of body-MATERIALS AND METHODS weight change may influence WGR.…”
mentioning
confidence: 99%